Analisis Pengaruh Kualitas Pelayanan, Harga Dan Fasilitas Terhadap Kepuasan Konsumen Pada Hotel Syariah Solo - Wardani, Ary Kusuma; , Muhammad Sholahuddin SE, M. Si (2016)
This study aimed to determine the effect of service quality, price, amenities on customer satisfaction in the hotel Shariah solo. The sample in this research was the respondents who've come and stay at Hotel Syariah Solo. But in this study using a study with a target object on surrounding communities solo ever came to the hotel shariah. The spread of the questionnaire is not necessarily done at the hotel with a view and deliver directly to the visitors who come to the hotel where shariah. The assumptions used are communities around solo who already know about the syariah hotel and never visited and stayed at the Hotel Syariah Solo totaling 96 respondents. The sampling technique in this research is accidental sampling. Data analysis method used is validity, reability, normality test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed the quality of service, price, and the facilities have significant influence with t respectively 2,285, 5,494 and 2,473. In the F test showed that together the variables of service quality, price, and facilities significantly influence purchasing decisions with a probability value of 0.000 (0.000 <0.05). The coefficient of determination (R2) of 54.9%.